PENGARUH MANAJEMEN KEUANGAN DAN MANAJEMEN SARANA PRASARANA TERHADAP MUTU PROSES PEMBELAJARAN PADA SEKOLAH DASAR DI WILAYAH UNIT PENGAWAS TINGKAT DINAS (UPTD) PENDIDIKAN BALONGAN KABUPATEN INDRAMAYU - Koridin Koridin; Wresni Pujiyati (STKIP Subang, 2019)
This study aims to determine the effect of financial management and infrastructure management on the quality of the learning process in elementary schools in the area of UPTD Education Balongan. The method used descriptive analysis uses a quantitative approach. Data analysis techniques using regression analysis techniques. The findings of this study are financial management, facilities and infrastructure management and the quality of the learning process have been carried out well; (1) Financial management has a significant effect on the quality of the learning process (2) Infrastructure management has an influence on the quality of the learning process and shows a significant relationship, (3) Financial management and infrastructure management together have a significant effect on the quality of the learning process teachers are expected to improve and create a learning atmosphere.